Financial Performance Analysis: A Case Study of PT Adhi Karya (Persero) Tbk and Listed Construction Companies in Indonesia with Dupont Analysis - Fardhiani, Nabilla Nur (Jurnal sosial dan sains, 2025)
This study evaluates the financial performance of PT Adhi Karya (Persero) Tbk (ADHI) compared with other listed construction companies in Indonesia from 2018 to 2024, using financial ratio analysis and the DuPont framework. The study employs a quantitative descriptive approach with secondary data from annual reports to analyze liquidity, profitability, leverage, activity, and market ratios—establishing benchmark comparisons with PTPP, TOTL, JKON, and NRCA. The findings reveal that ADHI consistently underperforms its industry peers, especially in profitability and asset efficiency. Although the company exhibits a high equity multiplier, the benefits of leverage are offset by a weak net profit margin and low total asset turnover, resulting in unsustainably low return on equity (ROE). The DuPont analysis further shows that ADHI’s financial challenges stem from operational inefficiencies, prolonged project cycles, and heavy reliance on debt financing. Business risks are amplified by long collection periods, delayed payments, and high working-capital pressure, while financial risk increases due to elevated debt ratios and volatile earnings. The study concludes that improving ADHI’s performance requires strengthening cost control, accelerating project execution, optimizing asset utilization, and rebalancing the capital structure to reduce leverage dependence.